Profession‐centric measures and indicators for occupational stress: An empirical study with novice software developers in Mexico - Ramon Palacio; Gilberto Cordova; Luis A. Castro; Gilberto Borrego (IET Software)
Abstract Occupational stress refers to job‐related uneasiness and anxiety, which affect people's emotional or physical health. Although occupational stress has been studied in several industries, it has remained largely unexplored in software developers, particularly in emerging economies such as Mexico. In this work, we propose a set of measures for supporting the assessment of occupational stress in software developers, which concurs with the types of tasks performed by software developers daily. For this, we first identified several stressors found in the literature. Then, we carried out 10 semi‐structured interviews with novice software developers to further understand stressors at the workplace. Afterwards, we conducted a study with 30 novice software developers for associating stress with workplace measures. From our work, we identified the workload, mental work fatigue, and work distraction as relevant measures associated with a certain level of stress in software developers. Our results suggest that some indicators can be used to monitor measures that are associated with occupational stress in software developers.